Central Disorders of Hypersomnolence, Restless Legs Syndrome, and Surgery With General Anesthesia: Patient Perceptions - LaBarbera, Vincent; García, Paul S.; Bliwise, Donald L.; Trotti, Lynn M. (Frontiers in Human Neuroscience, 2018)
Introduction: The importance of obstructive sleep apnea in patients undergoing surgery with general anesthesia is well-defined, but the surgical and anesthetic implications of other sleep disorders are less clear. We sought to evaluate response to surgery with general anesthesia in patients with central disorders of hypersomnolence or restless legs syndrome. Methods: We surveyed patients on their most recent surgical procedure with general anesthesia, querying about procedure, recovery, and any changes in sleep disorder symptomatology following the procedure. Results: Forty-five patients with restless legs syndrome and 57 patients with central disorders of hypersomnolence (15 narcolepsy type 2, 1 narcolepsy type 1, 30 idiopathic hypersomnia, 1 Kleine-Levin syndrome, and 10 subjective sleepiness) completed the survey, with response rates of 45.5% and 53.8%, respectively. While patients in both groups were equally likely to report surgical complications and difficulty awakening from anesthesia, hypersomnolent patients were more likely to report worsened sleepiness (40% of the hypersomnolent group versus 11% of the RLS group, p = 0.001) and worsening of their sleep disorder symptoms (40% of the hypersomnolent group versus 9% of the RLS group, p = 0.0001). Conclusion: Patients with sleep disorders other than sleep apnea frequently report surgical or anesthetic complications. Patients with hypersomnolence disorders commonly perceive that their sleep disorder worsened following a procedure; whether this might be related to long term effects of general anesthesia in a particularly vulnerable clinical population requires further study.